Building a central vascular access device registry in an adult intensive care unit: feasibility study - Mari Takashima, Nicole C Gavin, Emily N Larsen, Sarah Northfield, Gabor Mihala, Amanda Corley, Marc Ziegenfuss, Claire M Rickard (Vascular Access, 2018)
Introduction: Central venous access devices (CVAD) provide vascular access for the majority of intensive care patients. However, no comprehensive registry for CVAD insertion, complications and failure currently exists for research and quality assessment purposes in Australia. The primary aim of this study was to examine the feasibility of a CVAD registry to measure peripherally inserted central catheter (PICC) outcomes. Methods: In this feasibility study, intensive care unit (ICU) patients undergoing PICC insertion within an Australian tertiary-referral hospital were included. Data was extracted from the electronic medical record (EMR) and post-ICU discharge from ward paper medical records until removal of PICC, patient transfer to another hospital/facility, or death. The primary outcome was registry feasibility according to published criteria for national clinical quality registries. Secondary outcomes included: PICC utilisation ratio; PICC numbers and days; details of patients and PICCs; reason for PICC removal; and PICC failure/1000 catheter days. Results: Three out of seven feasibility criteria were not met: operational requirement, capturing necessary data, and infrastructure. Many patients were transferred to other wards, and the lack of an EMR in this setting meant 22% of PICCs were lost to follow-up due to unavailable records. However, for insertion-only data, six out of seven feasibility criteria were met, except for operational requirements, which could be solved by restructuring of the EMR.  Conclusion: A CVAD registry capturing data until PICC removal is only feasible if EMR is used throughout the hospital. The adoption of registry fields into the EMR will enable auto-population of a CVAD registry. Keywords: Central vascular access device registry, feasibility, peripherally inserted central catheter, complication.